Analisis Interferensi Fonetik Bahasa Ibu Tehadap Pelafalan Fonem Bahasa Arab dalam Pembelajaran Kosakata - Nailurrahmi, Fitma; Marlina, Lina (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
This research aims to identify forms of first language phonetic interference occurring in the pronunciation of Arabic phonemes, analyze common error patterns encountered, and uncover factors contributing to interference in vocabulary learning at Al-Mumtaaz Islamic Elementary School. The research method employed is a qualitative phenomenological approach, with data collection techniques including participatory observation, in-depth interviews, and document analysis.The findings indicate that phonetic interference manifests as phoneme substitution, sound distortion, epenthesis (sound addition), and intonation changes. Pronunciation errors most frequently appear in phonemes absent in the Indonesian language, such as /ق/, /ص/, /خ/, /ع/, /ذ/, and /ث/, which are replaced by the closest phonemes from the first language. The primary causative factors are differences in phonetic systems, insufficient articulation practice, and the dominance of the first language in students' daily lives. The implications of these findings underscore the importance of integrating phonetic training into Arabic vocabulary instruction at the elementary level to prevent pronunciation errors from becoming permanent.